Capital accumulation and work in China's internet content industry: Struggling in the bubble. (December 2018) - Xia, Bingqing
Since 2015, Baidu, Alibaba, and Tencent (the so-called BAT) have constructed an empire in the Chinese Internet content industry via mergers and acquisitions. However, little is known about how professional Internet workers are experiencing this process of accumulation and consolidation. This article focuses on how social relations are reconfigured and subsumed in the capital accumulation process in the realm of the Internet content industry, using the Chinese case. It argues that fresh graduates are subsumed into the accumulation process as immaterial resources in the circulation of capital. It also offers a general critique of the capital accumulation process, as it shifts risks and costs of failure on to independent start-ups entering the industry. JEL Codes: P34, O3, Z1